Impact of drugs on venous thromboembolism risk in surgical patients - Kovačič, Alenka Premuš Marušič; Caprnda, Martin; Mrhar, Aleš; Kubatka, Peter; Locatelli, Igor; Zoľáková, Barbora; Gaspar, Ludovit; Prosecký, Robert; Kruzliak, Peter; Staffa, Robert; Rodrigo, Luis; Radonak, Jozef; et al. (European journal of clinical pharmacology, 2019)
PURPOSE: This review focuses on the most common drugs administered to surgical patients during the perioperative period that affect the risk of venous thromboembolism (VTE). RESULTS: Among analgesics, the risk of VTE is increased in patients treated with diclofenac, ibuprofen, and rofecoxib, but not naproxen, while metamizole can confer a protective effect. The relationship between sedatives and VTE has not been sufficiently studied. Tricyclic antidepressants, low-potency serotonin reuptake inhibitors, and antipsychotics have been associated with increased risk of VTE. The use of diuretics in the perioperative period is poorly researched; however, hyponatremia is considered a risk factor. Other factors that may influence the risk of VTE include bridging anticoagulation, allogeneic transfusion, and hemostatic management before surgery. Pharmacotherapy for HIV or cancer may also increase VTE risk. CONCLUSION: Increased monitoring for VTE is therefore advisable in surgical patients and those receiving antipsychotics, antidepressants, diuretics, or analgesics.
Keywords: analgetika; Risk Factors; kontraceptiva orální hormonální; Venous Thromboembolism; žilní tromboembolie; perioperační péče; Hormone Replacement Therapy; lidé; Humans; rizikové faktory; antidepresiva; hormonální substituční terapie; Analgesics; hypnotika a sedativa; Antipsychotic Agents; Diuretics; Antidepressive Agents; Perioperative Care; diuretika; Contraceptives, Oral, Hormonal; Hypnotics and Sedatives; antipsychotika